A rare case of X-linked centronuclear myopathy in a neonate - N., Santosh; Kyadiggeri, Ravi; Kadambi, Prahlad; Sriranjini, K. S.; Reddy, Apoorva Pallam (International Journal of Contemporary Pediatrics, 2025)
We present the case of a late preterm male neonate who was limp at birth requiring extensive resuscitation in delivery room, requiring mechanical ventilation requiring higher settings and progressively worsening respiratory failure. Investigative panel reports later showed that the baby had a X-Linked myotubular myopathy (XLMTM)-centronuclear myopathy (CNM), which was the diagnosis responsible for the baby’s clinical presentation. Although CNMs do not have a specific treatment, early diagnosis of milder variants and understanding their pathophysiology helps in further facilitating diagnostic approach for the future.